Impact of Information and Communication Technologies (ICT) on Supply Chain Integration in Construction Projects - Quispe, Sergio (2025)
In recent years, the construction sector has undergone a significant transformation driven by digitalization. In this context, the use of Information and Communication Technologies (ICT) as a means of optimizing supply chain management (SCM) has gained particular relevance. These technologies have not only proven useful in improving traceability and efficiency in construction processes, but have also contributed to strengthening communication between the various stakeholders involved throughout the project lifecycle. Several recent studies have highlighted the benefits of digital tools such as BIM (Building Information Modeling), the Internet of Things (IoT), blockchain, and platforms. Collaborative technologies, which enable more integrated and transparent project management (Wu et al., 2022; Celik et al., 2023). This systematic review, based on the analysis of 30 scientific articles indexed between 2019 and 2024, shows that the application of these technologies favors interorganizational coordination, reduces the likelihood of errors, and increases the system's capacity to adapt to changes and unforeseen events (Hargaden et al., 2021; Fernandez-Carames et al., 2024). However, several challenges are also identified that hinder their implementation. These include a lack of common standards, resistance to change on the part of teams, high initial costs, and limited training in digital skills. Despite these barriers, researchers agree that establishing appropriate regulatory frameworks and strengthening digital governance can facilitate a more widespread adoption of ICTs in construction projects. This would allow to fully exploit its potential in the improvement and integration of the supply chain (Qian & Papadonikolaki, 2020; Sharma et al., 2023).